Malay and Arabic Terms in Muamalat Discourse: (Istilah Melayu dan Arab dalam Wacana Muamalat) (Jurnal Bahasa, 2014)
This study aims to identify the practical social manifestation of muamalat discourse which in the conventional economic system using Fairclough's Critical Discourse Analysis (CDA), and to analyse the textual features that underlie muamalat discourse within the framework of a conventional economic system. The discourse analysis method is used in this study. The text of the Operations Review of the Managing Director of Bank Islam Malaysia Berhad (BIMB) was used for the study. Results shows that social practice employed in muamalat discourse is a courtesy manifested through the use of words/terms. From a lexical aspect, it is revealed that muamalat discourse uses not only uncommon Malay words/terms and original Arabic words in the Malay text but also a combination of Malay-Arabic words/terms.Keywords: muamalat discourse; social practice; Critical Discourse Analysis; conventional economic system framework